Asymmetric N-Heterocyclic Carbene Catalyzed Annulation of 2-Alkenylbenzothiazoles with α-Chloro Aldehydes - Song, Xiaoxiao; Ni, Qijian; Zhu, Chen; Raabe, Gerhard; Enders, Dieter (Synthesis, 2015)
Diastereo- and enantioselective N-heterocyclic carbene catalyzed 1-azadiene Diels–Alder reactions of (E)-2-styrylbenzothiazoles with α-chloro aldehydes are reported. This annulation strategy provides an efficient access to medicinally important dihydrobenzothiazolopyridin-1-ones in good to excellent yields (44–97%) with very good to excellent stereoselectivities (up to 9:1 dr, 98% ee) and tolerates quite a range of substituents.
Keywords: N-heterocyclic carbenes; organocatalysis; asymmetric synthesis; aza-Diels–Alder reaction; annulation